A Literature Review of the Potential Diagnostic Biomarkers of Head and Neck Neoplasms - Konings, Heleen; Stappers, Sofie; Geens, Margot; De Winter, Benedicte Y.; Lamote, Kevin; van Meerbeeck, Jan P.; Specenier, Pol; Vanderveken, Olivier M.; Ledeganck, Kristien J. (Frontiers in Oncology, 2020)
Head and neck neoplasms have a poor prognosis because of their late diagnosis. Finding a biomarker to detect these tumors in an early phase could improve the prognosis and survival rate. This literature review provides an overview of biomarkers, covering the different -omics fields to diagnose head and neck neoplasms in the early phase. To date, not a single biomarker, nor a panel of biomarkers for the detection of head and neck tumors has been detected with clinical applicability. Limitations for the clinical implementation of the investigated biomarkers are mainly the heterogeneity of the study groups (e.g. small population in which the biomarker was tested, and/or only including high-risk populations) and a low sensitivity and/or specificity of the biomarkers under study. Further research on biomarkers to diagnose head and neck neoplasms in an early stage, is therefore needed.